Comunicación asertiva del docente y el clima emocional en el aula de preparatoria. - Becerra Amay, Nely María; Gonzáles López, Ginger Andreina (Machala, 2021)
"It is clear that you cannot talk about education without communication. They are two fields that have an eminently united link, all academic activities that are carried out day by day in the classroom require communicative interaction. For this reason, it is crucial that teachers have assertive tools to effectively fulfill their role as transmitter of knowledge and at the same time motivating and mediating in the interrelation with students. The main objective of this research was to determine the relationship that assertive communication has and the emotional climate of the classroom at the preparatory level, considering the great relevance it has in the educational field, which is why it will be useful for educators since it has scientific information validated on the most appropriate strategies to facilitate their teaching work. In this project, the importance of strengthening the classroom climate through assertive communication techniques is made known where the main protagonist is the teacher, he is in charge of using personal and didactic resources that facilitate his work, in addition to allowing the student build active learning in playful and harmonious spaces. The methodology used is of a qualitative nature since it allowed describing qualities and characteristics of the object of study, part of the hypothetical deductive method, the design is of a correlational descriptive nature, the population is made up of 6 teachers and the selected sample corresponds to 2 educators, for To collect the required information, a structured interview and an observation guide were applied to the teachers. With the results obtained, it is evidenced that there is a positive relationship between assertive communication and the emotional climate, for this reason it is concluded that by using this communicational ability the educational field will significantly favor the classroom climate. The review of scientific information in which all the theoretical contributions are closely related, also allowed to value assertive communication and recreational activities as vital pedagogical tools in the creation of positive classroom climates, which when converging provide the student with the possibility of enriching and build meaningful and lasting knowledge. Therefore, incorporating innovative strategies to improve teaching is an arduous task for the teacher. The main goal of them should be focused on promoting suitable learning environments in which students have the opportunity to build effective knowledge and in the future can turn them into the reality of his life, but for this it is essential that the teacher has updated pedagogical information that can be acquired through constant training; From this arises the need to propose training proposals through theoretical methodological workshops on assertive communication techniques, recreational activities and elements of the environment that promote a positive emotional climate in the classroom, which awakens in students the thirst for knowing and learning ."
Es claro que no se puede hablar de educación sin la comunicación son dos campos que tiene un vínculo eminentemente unido, cada actividad académica que se realiza a día con día en el aula requiere de la interacción comunicativa. Por ello es crucial que el docente disponga de herramientas asertivas para cumplir con eficacia su rol de transmisor de conocimientos y a la vez motivador y mediador en la interrelación con los estudiantes. El principal objetivo de esta investigación fue determinar la relación que tiene la comunicación asertiva y el clima emocional del aula en el nivel preparatoria, considerando la gran relevancia que tiene en el ámbito educativo, por lo cual será útil para los educadores ya que posee información científica validada sobre las estrategias más adecuadas para facilitar su labor de enseñanza. En este proyecto se da a conocer la importancia de fortalecer el clima del aula mediante técnicas de comunicación asertiva donde el protagonista principal es el docente, él es el encargado de emplear recursos personales y didácticos que faciliten su labor, a más de ello permitir al estudiante construir aprendizajes activos en espacios lúdicos y armónicos. La metodología utilizada es de carácter cualitativo puesto que permitió describir cualidades y características del objeto de estudio, parte del método hipotético deductivo, el diseño es de carácter descriptivo correlacional, la población está constituida por 6 docentes y la muestra seleccionada corresponde a 2 educadoras, para recabar la información requerida se empleó una entrevista estructurada y una guía de observación a las docentes. Con los resultados obtenidos se evidencia que existe una relación positiva entre la comunicación asertiva y el clima emocional, por ello se concluye que al emplear esta habilidad comunicacional el campo educativo favorecerá de manera significativa el clima del aula. La revisión de información científica en la cual todos los aportes teóricos guardan estrecha relación, permitió valorar también a la comunicación asertiva y a las actividades lúdicas como herramientas pedagógicas vitales en la creación de climas áulicos positivos, mismas que al converger proporcionan al alumno la posibilidad de enriquecer y construir conocimientos significativos y duraderos. Por consiguiente incorporar estrategias innovadoras para mejorar la enseñanza es tarea ardua del docente la meta principal de ellos debe estar enfocada en propiciar ambientes de aprendizajes idóneos en el cual los estudiantes tengan la oportunidad de construir conocimiento efectivos y en un futuro puedan volcarlos a la realidad de su vida, pero, para ello es indispensable que el profesor posea información pedagógica actualizada misma que puede adquirir a través de constante formación; de ello surge la necesidad de plantear una propuestas de capacitación a través de talleres teóricos metodológicos sobre técnicas de comunicación asertiva, actividades lúdicas y elementos del entorno que propician un clima emocional positivo en el aula, que despierte en los educandos la sed por conocer y aprender."
Keywords: COMUNICACION; ASERTIVIDAD; CLIMA EMOCIONAL